Local Wisdom of The Agriculture System in Tukang Besi Islands Community (Case Study at Wangi-Wangi Island Wakatobi Regency) - Harviyaddin, Harviyaddin; Hidrawati, Hidrawati; Manan, Abdul; Sabaruddin, Laode; Safuan, Laode; Arafah, Nur; Mappasomba, Musadar (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2020)
Local wisdom of the community in the agricultural system gains a large number of interests in the field of research because of its ties to the aspects of ecology, economy, and socio-culture. This study aims to analyze Tukang Besi islands community's local wisdom and its role in sustainable agriculture systems. This research was conducted from May to December 2018. The data was collected through orientation, exploratory, and confirmative studies, thus analyzed in qualitative descriptive method by describing local wisdom and its role in sustainable agricultural system. The results showed that agriculture is a way of life for the community in Wangi-Wangi Island. The practice of agronomic local wisdom in cassava cultivation is ecologically, economically, socially and culturally appropriate. Local wisdom is practiced starting from the selection and determination of land, land clearing, planting, maintenance and harvesting. Local wisdom of the Wangi-Wangi Island community in a sustainable agricultural system has three roles: 1) ecologically by maintaining the preservation of land resources through conservation in the welli'a and rawu'a systems by integrating plant diversity, mulching, and fallowing; 2) economically by maintaining the sources of life such as food reserves and alternative sources of income through the collection of forest and marine products, and 3) socially by maintaining a socio-cultural system in harmonious relations between the Sara and the community and by maintaining the stability of production.